2010
DOI: 10.1007/s00125-010-1817-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of increased islet cell proliferation in patients with recent-onset type 1 diabetes

Abstract: Aims/hypothesis In adults, the rate of beta cell replication is normally very low, but recent evidence suggests that it may increase during insulitis. We therefore studied tissue from donors with recent-onset type 1 diabetes to establish whether islet cell proliferation is increased during the disease process. Methods Paraffin-embedded pancreatic sections from ten donors with recent-onset type 1 diabetes and a range of relevant controls were stained by immunohistochemical techniques with antibodies against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 24 publications
6
82
1
3
Order By: Relevance
“…A detection system (REAL Envision; Dako, Cambridge, UK) was used for antigen detection. For details of human donors [27][28][29], see ESM Methods and ESM Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…A detection system (REAL Envision; Dako, Cambridge, UK) was used for antigen detection. For details of human donors [27][28][29], see ESM Methods and ESM Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Willcox and coworkers (45) demonstrated that in type I diabetes Alpha and Beta cells undergo an increase in proliferation during progression. These cells show a high level of coexpression of Ki67 and MCM which are indicative of a proliferative response in an autoimmune attack during the course of diabetes type I. Qian and colleagues (44) showed that MCM complex can be effective in understanding the pathogenesis of many viral diseases.…”
Section: Expression Of MCM Protein Family As a Biological Marker Of Pmentioning
confidence: 99%
“…The  cell deficit in type 1 diabetes is related to the established autoimmune destruction of the target cells. However, several lines of research indicate that some  cell regeneration may occur in recent onset type 1 diabetic patients (Willcox et al, 2010) and even in patients with long-standing type 1 diabetes (Meier et al, 2005). The failure of  cell regeneration in type 1 diabetes may be related to the increased vulnerability of the newly forming  cells to apoptosis induced by inflammatory cytokines (Meier et al, 2006).…”
Section:  Cell Mass In Type 1 and Type 2 Diabetesmentioning
confidence: 99%